Civil Society Organizations and Their Roles in Alcohol Control in Thailand - Saengow, Udomsak (Area Based Development Research Journal, 2020)
A civil society is an area of culture that is not part of either the state or business institution. Civil society organizations (CSOs) generally play a role in improving living conditions of those who cannot access public services and market-provided services. In 1990s, CSOs increased involvement in public health issues; because activities of a civil society are consistent with public health activities based on the concept of community health. Additionally, in 1990, civil society in Thailand played an important role in political movement. The political climate during the enactment of the Constitution for the Kingdom of Thailand 1997 supported participation of civil society in several aspects and led to establishment of Thai Health Promotion Foundation. The Thai Health Promotion Foundation has become a primary source of funding for many CSOs as funding from international organizations decreased. CSOs integrated focus on issues with health promotion, a primary focus of the Thai Health Promotion Foundation. In regard, for example to alcohol control, CSOs that worked on religion, domestic violence as well as youth leaders develop as CSOs on alcohol control. Activities such as the Buddhist Lent Abstinence Campaign emerged from the integration of Buddhism and alcohol prevention campaign. Alcohol control CSOs supported state actions in reduction of alcohol-related problems. Consequently, the Buddhist Lent Abstinence Campaign, primarily administered by CSOs, has been proven successful in the reduction of alcohol consumption during the campaign period.